Adult exposure to bisphenol A in rare minnow Gobiocypris rarus reduces sperm quality with disruption of testicular aquaporins. (February 2018) - Zhang, Yingying; Guan, Yongjing; Zhang, Ting; Yuan, Cong; Liu, Yan; Wang, Zaizhao
Abstract: Bisphenol A (BPA) is an endocrine disrupter which has adverse effects on male reproduction. Aquaporins (AQPs), well known water-selective channels, play important roles in spermatogenesis and sperm functions. However, whether AQPs participate in the process that BPA induces abnormal sperms has not been investigated to date. In the present study, adult male rare minnows Gobiocypris rarus were exposed to environmentally relevant concentrations BPA (15 and 225 μg/L) for 1, 2 and 3 weeks. Results showed that BPA exposure disrupted sperm motility, increased the percentage of abnormal sperm cells, and decreased sperm tolerance to hypotonic solution and sperm fertilization capacity. Meanwhile, protein levels of AQPs were up-regulated, and their distribution in the testis was abnormal following BPA exposure. The following chromatin immune coprecipitation showed that BPA could regulate aqp3 and 8 expression through the ERE in their 5′-flanking region. The present study demonstrated that BPA could decrease the sperm quality in rare minnow, and AQP3 and 8 might play significant roles in this process. Highlights: BPA exposure disrupted sperm motility, increased abnormal sperm. BPA decreased sperm hypotonic tolerance and fertilization capacity. BPA could regulate aqp3 and 8 through ERE in their 5′-flanking region. Aqp3 and 8 may play significant roles in BPA decreased sperm quality.